EFEKTIVITAS PENYULUHAN KESEHATAN REPRODUKSI REMAJA TERHADAP TINGKAT PENGETAHUAN SISWA SMAN 6 KECAMATAN PONTIANAK TIMUR TAHUN 2013 - ., Frisa Buzarudina (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Adolescent is a large component in Indonesia. As the nextgeneration, adolescent should be able to avoid the problems along theirtransition term. The problems are including sexuality problems, unwantedpregnancies and abortions, infected by Sexual Transmitted Diseases, anddrug abuse. Wrong information about sexuality can lead wrongknowledge and perceptrion to adolescents. This be one of some indicatorsthat increased sexuality behaviour in adolescenst. Based on research,knowledge about reproductive health influences reproductive behaviour.Objective: To find out the effectivity of counseling about adolescentreproductive health to knowledge level of Senior High School Number 6sstudents age 15 to 18 years at East Pontianak District in 2013.Methods: This research is use quasy experimental method with one grouppretest-postest design to 89 respodents. For hipothesis testing useWilcoxon test.Results: Significancy value from Wilcoxon test is 0,000 (p<0,05), thatmeans there is a significant difference in scores between before and afteradolescent reproductive health counseling Conclusions: Adolescent reproductive health counseling is effective toincrease respondents knowledge about adolescent reproductive health.Keywords: adolescent reproductive health, counseling, adolescentNotes: 1. Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Borneo2. Department of Public Health, Faculty of Medicine, University ofTanjungpura, Pontianak, West Borneo